Language use in the construction of interpersonal relationships electronic English in Malaysia - Hashim, A. (2012)
The Internet has come to dominate our lives and emerged as one of the key communication technologies. Since the Internet is a medium which can be considered revolutionary and is therefore bound to have a profound effect on language, it is crucial to evaluate and study its impact on language. Although many have noted the linguistic changes emerging in online communication, not many have studied the phenomenon and written about it. This study examines the extent to which the Internet fosters diversity of languages or English dominance. In addition, it looks at how standard English competes with various varieties of English in online realms in Malaysia and the complex interrelationship between the Internet and English language variation in Malaysia.